2005
DOI: 10.1037/0021-9010.90.5.827
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Examination of the Relationships Among Training Outcomes, Mediating Regulatory Processes, and Adaptive Performance.

Abstract: This study examined whether cognitive, affective-motivational, and behavioral training outcomes relate to posttraining regulatory processes and adaptive performance similarly at the individual and team levels of analysis. Longitudinal data were collected from 156 individuals composing 78 teams who were trained on and then performed a simulated flight task. Results showed that posttraining regulation processes related similarly to adaptive performance across levels. Also, regulation processes fully mediated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
205
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(214 citation statements)
references
References 50 publications
7
205
0
2
Order By: Relevance
“…Teamwork collective effi cacy was related to individual teamwork behaviour and to team performance of business students (Tasa, Taggar, & Seijts, 2007). Collective effi cacy was related to team adaptive performance of undergraduates learning a fl ight-simulation task (Chen, Thomas, & Wallace, 2005). Research has also suggested, although to a lesser extent, that perceived competence of one's team members may be associated with decreased burnout.…”
Section: Team Effi Cacymentioning
confidence: 99%
See 1 more Smart Citation
“…Teamwork collective effi cacy was related to individual teamwork behaviour and to team performance of business students (Tasa, Taggar, & Seijts, 2007). Collective effi cacy was related to team adaptive performance of undergraduates learning a fl ight-simulation task (Chen, Thomas, & Wallace, 2005). Research has also suggested, although to a lesser extent, that perceived competence of one's team members may be associated with decreased burnout.…”
Section: Team Effi Cacymentioning
confidence: 99%
“…We also have extended the work on team and collective effi cacy (e.g., Chen et al, 2005;Tasa et al, 2007) by using a nonstudent sample, and examining the relationship of team effi cacy with individual health outcomes. We also extended past work on the moderating effects of effi cacy (see Grau et al;Jex & Bliese, 1999) by examining this construct in the context of its ability to buffer the negative effects of specifi c safety and psychosocial stressors (which were relevant to AMH professionals) on burnout.…”
Section: Contributions To Scholarshipmentioning
confidence: 99%
“…Second, we make a specific contribution to research on expertise that has largely focused on experts' knowledge and problem-solving skills observed in individual task settings but largely neglected experts' behavior unfolding in a team context (Ericsson & Lehmann, 1996). Third, by focusing on professionals working together in organizational settings over longer periods, we go beyond earlier research that has often included students working together in laboratory or simulation settings (Chen et al, 2005;DeShon et al, 2004;Tasa et al, 2007). Fourth, our longitudinal study overcomes limitations of previous studies that have examined the association between individual characteristics and contributions to teams with cross-sectional designs (Barry & Stewart, 1997;Morgeson, Reider, & Campion, 2005).…”
mentioning
confidence: 99%
“…One aspect within this multilevel conceptualization of teams refers to individual-level processes that unfold within a team context. An increasing number of studies has not only considered team processes at the team level but also examined individual-level processes within the team context (Chen, Thomas, & Wallace, 2005; DeShon, Kozlowski, Schmidt, Milner, & Wiechman, 2004;Ng & Van Dyne, 2005).…”
mentioning
confidence: 99%
“…To develop emotional skills, training programs should teach leaders to identify emotions, use emotions to facilitate thought, understand emotions, and manage emotions (Caruso & Wolfe, 2004). Finally, it is important to note that training programs aimed at maximizing adaptive capabilities also should enhance self-regulatory and metacognitive skills to achieve learning outcomes and performance goals (e.g., Chen, Thomas, & Wallace, 2005;Kozlowski, 1998;Salas, Burke, & Stagl, 2004). That is, leaders, who monitor and regulate their own learning, have a better understanding of the task domain and can better acquire and integrate key skills and promote adaptive team performance (Kozlowski, 1998;Salas, Burke, & Stagl, 2004).…”
Section: Recommendations For Training Adaptive Performancementioning
confidence: 99%